An Analysis of Modality in Emma Watson and Michael Kimmel’s Speech Texts - Aprilia, Lulu’ Ulfiyah; Misnadin, Misnadin (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2021)
This study used Palmer’s (1986) theory to analyzed Modality and Halliday (2008) to analyze the meaning of modality. Relating to the statements above, this study was proposed to answer two articulated research problems, namely; (1) what are the types of modality found in Emma Watson and Michael Kimmel’s Speech Texts? And (2) To what extent do Emma Watson and Michael Kimmel’s Speech Texts show similarities and differences, if any, in their use of types of modality? This study employs a descriptive qualitative design. The data were all of the speech by Emma Watson and Michael Kimmel’s Speech Texts that contain modality. In terms of types of modality, 30 data of modality were found. The data are classified into two types of modality: Epistemic modality consists of 10 data; judgments (5 data) and modifications (5 data). Deontic modality consists of 20 data; directives (3 data), modifications (4 data), subjectivity (5 data), imperatives (3 data), commissives (2 data), and volitives (3 data). Moreover, in terms of similarities and differences, the data are classified into two terms similarities and differences. We found 11 data of similarities and differences in types of modality: In terms of similarities in types of epistemic modality (3 data) and similarities in types of deontic modality (2 data). In terms of differences in epistemic modality (2 data) and differences in deontic modality (4 data). Keywords: Modality, Epistemic, and Deontic